2004
DOI: 10.1177/0095399703258776
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Risk Factors in the Development of Medial Tibial Stress Syndrome among Naval Recruits

Abstract: Identifying a pronated foot type prior to training may help reduce the incidence of medial tibial stress syndrome by early intervention to control abnormal pronation. Findings of a higher incidence of medial tibial stress syndrome among female recruits require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
334
6
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(358 citation statements)
references
References 50 publications
12
334
6
6
Order By: Relevance
“…The loading is also likely to be highest at regions of peak compressive forces and, to a lesser extent, tensile forces [24] but no investigations have performed a prospective detailed examination of the tibia in response to an arduous training programme. This is clinically important because the tibia is susceptible to stress injuries early in military training [32], which typically present at the posterior border of the distal third [32][33][34]. The primary purpose of this study was to examine site-and regional-specific adaptations of the tibia to arduous training in a cohort of male infantry recruits to better understand how bone responds in vivo to mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…The loading is also likely to be highest at regions of peak compressive forces and, to a lesser extent, tensile forces [24] but no investigations have performed a prospective detailed examination of the tibia in response to an arduous training programme. This is clinically important because the tibia is susceptible to stress injuries early in military training [32], which typically present at the posterior border of the distal third [32][33][34]. The primary purpose of this study was to examine site-and regional-specific adaptations of the tibia to arduous training in a cohort of male infantry recruits to better understand how bone responds in vivo to mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies have found that variations in weightbearing foot posture are associated with an increased risk of medial tibial stress syndrome in military recruits [1] and overuse leg injuries in triathletes [2]. These findings suggest that pes cavus (high medial longitudinal arch) and pes planus (low medial longitudinal arch) may display abnormal biomechanical parameters that predispose an individual to injury.…”
Section: Introductionmentioning
confidence: 99%
“…This finding demonstrated the FPI-6 being simple to use and reliable. Some studies have used the FPI to identify risk factors for sports-related injuries (Cain, Nicholson, Adams, & Burns, 2007;Yates & White, 2004). Yates and White (2004) found a positive correlation between pronated feet and medial tibial stress syndrome in naval recruits.…”
Section: Discussionmentioning
confidence: 99%